Quality of life in adult and pediatric patients with tropomyosin receptor kinase fusion cancer receiving larotrectinib - Kummar, Shivaani; Berlin, Jordan; Mascarenhas, Leo; Tilburg, Cornelis M. van; Geoerger, Birgit; Lassen, Ulrik N.; Schilder, Russell J.; Turpin, Brian; Nanda, Shivani; Keating, Karen; Childs, Barrett H.; Chirila, Costel; et al. (Current problems in cancer, 2021)
Neurotrophic tyrosine receptor kinase (NTRK) gene fusions lead to chimeric tropomyosin receptor kinase (TRK) fusion proteins, which act as primary oncogenic drivers in diverse tumor types in adults and children. Larotrectinib, a highly selective and central nervous system-active TRK inhibitor, has shown high objective response rates, durable disease control, and a favorable safety profile in patients with TRK fusion cancer. The impact of larotrectinib on health-related quality of life (HRQoL) was evaluated in adult and pediatric patients in two phase I/II clinical trials (NAVIGATE; NCT02576431 and SCOUT; NCT02637687). Patients completed HRQoL questionnaires (EORTC QLQ-C30, EQ-5D-5L, and PedsQL) at baseline and at planned treatment cycle visits. Changes in questionnaire scores were evaluated over time, and by tumor type and treatment response. Questionnaires from 40 adult and 17 pediatric (2-19 years of age) patients receiving larotrectinib were completed at baseline and at least one post-baseline timepoint. Meaningful within-patient HRQoL improvements occurred at one or more timepoints in 60% of adults and 76% of pediatric patients. Sustained improvements in EORTC QLQ-C30 and PedsQL scores were rapid, occurring within 2 months of treatment initiation in 68% and 71% of patients, respectively. Improvements were observed regardless of tumor type and appeared to correlate with clinical efficacy. The rapid within-patient HRQoL improvements in adult and pediatric patients with TRK fusion cancer are consistent with the clinical profile of larotrectinib. Our results provide valuable information for use of this agent in this patient population. A plain language summary of this article is available in the supplementary appendix.